Anti-thymoglobulin (ATG) treatment does not reverse type 1 diabetes in the acute virally induced rat insulin promoter-lymphocytic choriomeningitis virus (RIP-LCMV) model - Bresson, D; von Herrath, M.G (Clinical and experimental immunology, 2011)
Immune modulators such as anti-thymoglobulin (ATG) are under clinical evaluation for the treatment of type 1 diabetes (T1D). Although such agents have cured T1D in the non-obese diabetic (NOD) model, their clinical efficacy has been much lower. In order to improve the odds of successful translation from bench to bedside, we propose to evaluate this agent under more stringent conditions. Here, we evaluated the capacity of ATG to reverse T1D in the acute rat insulin promoter-lymphocytic choriomeningitis virus (RIP-LCMV) model. RIP-LCMV-glycoprotein (GP) mice were treated after new-onset T1D with murine ATG antibodies. Although ATG treatment did not impair viral clearance it failed to reverse new-onset T1D in this model. The CD4 : CD8 ratio was reduced drastically upon LCMV infection due to an expansion of CD8 effectors but ameliorated in ATG-treated mice. Although the percentage of CD4⁺CD25⁺ regulatory T cells (Tregs) within the CD4⁺ population was increased significantly after ATG therapy, their frequency in the periphery was reduced dramatically and never returned to normal baseline. The inability of ATG treatment to cure T1D in a stringent viral model (RIP-LCMV mice) is due at least partially to the inability to maintain or increase a sufficient CD4⁺CD25⁺ Tregs frequency, in striking contrast with what was reported in the NOD model. Our data would argue for the use of multiple animal models to assess efficacy of promising immune-based interventions and select the most potent therapies for future clinical trials.